THE LEGAL REGULATION AND PRACTICE OF SOCIOLOGICAL SUPPORT OF THE CAMPAIGN FOR THE ELECTION OF DEPUTIES OF THE STATE DUMA OF THE FEDERAL ASSEMBLY OF THE RUSSIAN FEDERATION ON DECEMBER 4, 2011 AND THE PRESIDENT OF THE RUSSIAN FEDERATION, ON MARCH 4, 2012 - Victoria A. Gorbatova (Сравнительная политика)
The present material introduces a piece of information about the RussianElectionTechnologiesTrainingCenterun182 der the CEC ofRussiasociological forecasts’ competitions, organized during the State Duma of Federal Assembly of the Russian Federation deputies’ elections on December 4, 2011 and the President of the Russian Federation elections on March 4, 2012. Some legal aspects of sociological services’ activity within domestic electoral process, including the organization of so-called exit polls are enlightened. A number of theoretical approaches and methodological problems during forming electoral forecasts are reviewed in short. The author denotes a high interest of expert and sociological organizations into the domestic electoral sphere. The article is supplied with the necessary illustrative graphics.